FTA contributes to shaping a peatland policy in Peru. Peatland have a strong role in mitigating the effects of climate change, preserving biodiversity, minimising flood risk, and ensuring safe drinking water - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
FTA research has contributed to Peru’s national Forest Reference Emission Levels (FREL) reported to UNFCCC, recognizing peatlands in Amazonia for their environmental importance and climate change mitigation potential.